Numerical Simulation of HVAC System Functionality in a Sociocultural Building. (2016) - Popovici, Cătălin-George; Hudişteanu, Valeriu Sebastian
Abstract: The study presents the functionality of the heating, ventilation and air conditioning (HVAC) system for an important and prestigious objective of Iasi, the "Vasile Alecsandri" National Theatre. A numerical model was created, for the indoor climate analysis, obtaining the main thermal comfort parameters, in different zones of the auditorium. The model carried out on the CFD tool ANSYS-Fluent, is based on the recently implemented HVAC system of the theatre. The results are presented comparatively in two distinct scenarios of the ventilation and conditioning system: when the theatre is occupied and during the breaks. Results from simulation showed that the system provides suitable conditions for occupants and decorative finishing.